Geoquímica de litologias básicas e ultrabásicas da unidade de alóctone superior do maciço de Bragança - Santos, José Francisco Horta Pacheco dos
The Galicia - Tras-os-Montes Zone is composed of several exotic tectonic units emplaced upon the Central-Iberian autochthon. The upper allochthonous thrust complex crops out in the Bragança Massif, where it is represented mainly by several lithologies of dominantly mafic and ultramak compositions: evidences of granulite-facies and eclogite-facies metamorphism are common. Four main rock tqpes were studied: 1) high-pressure granulites; 2) eclogites (enclosed by paragneisses); 3) plutonic bodies, essentially composed of gabbroic rocks, 4) ultramafic rocks. Previous works have shown that the first hvo lithotypes have passed through a complex tectonometamorphic evolution, leading some authors to propose models considering polycyclical tectonic models. However, the polycyclical hypothesis is apparently contradicted by the geochronological information available until now, which usually correspond to ages related to the Variscan cycle. According to the geochemical data, the compositions of high-pressure granulites seem to reflect fractionation processes under high-grade metamorphic conditions; redistribution of highly incompatible trace elements (including some elements that are not easily transported by the most common metamorphic fluids) would have occurred, at least locally. The trace element contents of ditferent types of granulites (from mafic to felsic), when compared to the most basic compositions amongst those that are proposed to represent the lower crust, display LREE-depleted patterns, suggesting that, besides being reinobilize& the most incompatible elements have suEered removal, . probably via a silicate liquid phase. Isotope Sm-Nd analyses were performed using one sample of mafic granulite from the Tojal de Pereiros outcrop: a wr-mineral 1079*78 Ma isochron was obtained The dated granulite has neither mineral relics nor texwral features hpthetically related to the protolithi consequentl!: the geochronological datum marks Nd-isotope homogenization during a metamorphic event. Therefore. high-pressure granulites represent fragments of Grenviilian basement that were reactivated and eshumed during the Variscan orogeny. Resunzo -Abstract I11 Three main compositional groups of eclogites were defined using hygromagmatophile trace elements with essentially imrnobile behaviour in metamorphic processes: A) rocks of tholeiitic composition, similar to N-MORB; B) subalkaline (tholeiitic to calc-alkaline) rocks displaying geochemical signatures typical of supra-subduction settings; C) rocks related to alkaline basalt protoliths. The diversity revealed by the eclogites together with the geochemical features of the enclosing paragneisses (characteristic of sediments from basins related to volcanic arcs) suggest that the protoliths of the metaigneous and metasedimentav rocks were formed in a back-arc marginal basin. Isotope data from an eclogite sample reveals that the Sm-Nd system has been disturbed: however, the wr-grt line indicates that the high-pressure metamorphic event is older than 508 Ma. A 389+10 Ma wr-mineral isochron was obtained using a sample of a metasomatic vein in granulitized eclogite. The occurrence of the metasomatic event was determined by the penetration, in the metabasites, of aqueous fluids generated by devolatilization reactions in-the enveloping paragneisses during decompression. The Lower Devonian age clearly does not date the eclogitization; instead, it corresponds to a later metamorphic episode. Previous authors have emphasized that the gabbroic plutonic bodies, compared to highpressure granulites and eclogites, had a simpler tectonothermal evolution and that ihey postdate the earliest defonnation phases recorded in the HP metamorphic rocks. Trace-element and isotope compositions of gabbroic rocks indicate that they crystallized from continental tholeiitic magmas; the %d VS. features reveal interaction with metamorphic rocks with long-term lower-crust residence. Sm-Nd data suggest that igneous emplacement would have occurred during Upper Precambrian or Cambrian times; an internal wr-mineral isochron shows that the closure of the Sm-Nd system after partial granulitization (responsible for corona textures) has an Ordovician age; another internal Sm- Nd isochron (obtained in a flasergabbro) may represent an early phase (Upper Silurian age) of tectonic uplift. Isotope data, together with petrographic information collected in the gabbroic samples, reveal that micro-domainal readjustments play a significant role in rocks that were affected by partial mineralogical and textural transformations. Ultramafic rocks - in part, at least - represent a portion of subcontinental lithospheric upper mantle, located in an intraplate tectonic setting in the Lower Palaeozoic. Intimately associated peridotite and pyroxenite layers are probably testimonies of the penetration of magmas (from which pyroxenes were segregated) through rocks (of harzburgitic or similar compositions) previously submitted to melt removal. Some pyroxenite bodies are well individualized and may contain garnet; . this type of pyroxenites has traceelement patterns characteristic of their derivation from alka1'me magmas; the ascent of strongly LREEenriched melts through upper mantle rocks, besides being responsible for the generation of those bodies, could also have caused cryptic metasomatism preferentially affecting the refractory lithologies. A garnet clinopyroxenite sample displayed a 485+17 Ma wr-mineral isochron (Sm-Nd system), implying that the presence of the alkaline magmas occurred during the Lower Ordovician or earlier; therefore, this type of pyroxenites corresponds to deep manifestations of the igneous phenomena that accompanied the extensional period marking the beginning of the Variscan tectonic cycle. The results of this work, together with other geological evidences previously presented, agree with the polycyclical evolution hypothesis for the upper allochthonous thrust complex of NW Iberia. The scarcity of geochronological results showing the occurrence of Precambrian metamorphic events is probably due to the thermal effects of the very important Lower Palaeozoic magmatism and to the intense Variscan orogenic remobilization.